Association between SARS-CoV-2 infection and newly diagnosed hypertension during pregnancy: prospective, population based cohort study - Olof Stephansson; Jonas Söderling; Kari Johansson; Anna Sandström; Anne K. Örtqvist; Maria C. Magnus; Elisabeth Dahlqvist; Siri E. Håberg (BMJ Medicine, 2023)
Objective To study the association between SARS-CoV-2 infection and newly diagnosed hypertension during pregnancy.Design Prospective, population based cohort study.Setting All singleton pregnancies after 22 completed gestational weeks registered in the Swedish Pregnancy Register and the Medical Birth Registry of Norway, from 1 March 2020 to 24 May 2022.Participants 312 456 individuals available for analysis (201 770 in Sweden and 110 686 in Norway), with pregnancies that reached 42 completed gestational weeks by the end of follow-up in the pregnancy registries, excluding individuals with SARS-CoV-2 infection before pregnancy and those with a diagnosis of pre-existing hypertension or onset of hypertension before 20 gestational weeks.Main outcome measures Newly diagnosed hypertension during pregnancy was defined as a composite outcome of a diagnosis of gestational hypertension, pre-eclampsia, HELLP (haemolysis, elevated liver enzymes, low platelets) syndrome, or eclampsia, from gestational week 20 to one week after delivery. The association between SARS-CoV-2 infection and hypertension during pregnancy was investigated with a stratified Cox proportional hazard model, adjusting for maternal age, body mass index, parity, smoking, region of birth, education, income, coexisting medical conditions, previous hypertension during pregnancy, number of healthcare visits during the past year, and vaccination against SARS-CoV-2. Pre-eclampsia was also analysed as a separate outcome.Results Of 312 456 individuals available for analysis, 8% (n=24 566) had SARS-CoV-2 infection any time during pregnancy, 6% (n=18 051) had a diagnosis of hypertension during pregnancy, and 3% (9899) had pre-eclampsia. SARS-CoV-2 infection during pregnancy was not associated with an increased risk of hypertension during pregnancy (adjusted hazard ratio 0.99, 95% confidence interval 0.93 to 1.04) or pre-eclampsia (0.98, 0.87 to 1.10). The results were similar for SARS-CoV-2 infection in all gestational trimesters and in different time periods that corresponded to dominance of different variants of the SARS-CoV-2 virus.Conclusions This population based study did not find any evidence of an association between SARS-CoV-2 infection during pregnancy and an increased risk of hypertension during pregnancy or pre-eclampsia.